PENGEMBANGAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) BERBASIS EKONOMI KREATIFOLEH DINAS PERDAGANGAN PERINDUSTRIAN, KOPERASI USAHA KECIL DAN MENENGAH - Ade Satya Pratama; Yenni Jufri; Yurismen Effendi (Jurnal Public Administration, Business and Rural Development Planning, 2022)
Based on the descriptions in the previous chapters, the authors draw the following conclusions: 1) Development of Micro, Small and Medium Enterprises (MSMEs) based on creative economy by the Department of Trade, Industry, Small and Medium Enterprises Cooperatives of Sijunjung Regency. (Case Study On By By Sijunjung Kalamai Urang Awak) are as follows; a) Increasing market access and increasing market share, the Kalamai urang crew distributes their products to various distributor areas, even to Palembang and Jambi. SMEs Kalamai Urang Awak Sijunjung Regency in increasing their market access participated in a bazaar held by the Office of Trade, Industry, Small and Medium Enterprise Cooperatives of Sijunjung Regency, b) Increasing access to capital sources and strengthening the capital structure, the business capital of Kalamai Urang crew came from one owner and no outside help. c) Improving organizational and management capabilities, that in order to improve organizational capability the Kalamai Urang Awak leadership of Sijunjung Regency sent its members to attend trainings held by the Department of Trade, Industry, Small and Medium Enterprise Cooperatives of Sijunjung Regency such as product marketing, product pachaging training, product quality training, and product development training. d) Increasing access and mastery of technology, that the marketing technology used by SMEs is kalamai urang crew with social media such as Instagram and Facebokk. Technology for the production of MSMEs still does not use sophisticated technology. Based on the conclusions above, the authors provide the following suggestions: 1) The Office of Trade, Industry, Small and Medium Business Cooperatives in Sijunjung Regency as the person in charge of developing and empowering MSMEs based on the creative economy in Sijunjung Regency should provide adequate facilities and infrastructure, so that MSME actors creative economy-based companies can develop and market their products effectively. 2) The people of Sijunjung Regency as MSME actors based on the creative economy should open their minds not to be pragmatic in accepting the empowerment provided by the government.